2017
DOI: 10.1016/j.matlet.2016.10.122
|View full text |Cite
|
Sign up to set email alerts
|

ZrB2-HfB2 solid solutions as electrode materials for hydrogen reaction in acidic and basic solutions

Abstract: Spark plasma sintered transition metal diborides such as HfB 2 , ZrB 2 and their solid solutions were investigated as electrode materials for electrochemical hydrogen evolutions reactions (HER) in 1 M H 2 SO 4 and 1 M NaOH electrolytes. HfB 2 and ZrB 2 formed complete solid solutions when mixed in 1:1, 1:4, and 4:1 ratios and they were stable in both electrolytes. The HER kinetics of the diborides were slower in the basic solution than in the acidic solutions. The Tafel slopes in 1 M H 2 SO 4 were in the range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…MXenes are therefore potentially promising 2D HER catalysts, but are limited to carbide, nitride, and carbonitride phases due to compositional limitations of the parent MAX phases. In addition to metal carbides, metal borides also have been gaining attention as HER catalysts, especially molybdenum borides that include α-MoB, β-MoB, Mo 2 B, and MoB 2 . , However, efforts to access high surface area metal boride materials are challenging, particularly for the molybdenum-based systems that are of greatest interest for their high activity and stability. The ability to access MXene-like 2D borides through etching boride analogues of MAX phases would significantly expand the diversity of available MXene materials .…”
mentioning
confidence: 99%
“…MXenes are therefore potentially promising 2D HER catalysts, but are limited to carbide, nitride, and carbonitride phases due to compositional limitations of the parent MAX phases. In addition to metal carbides, metal borides also have been gaining attention as HER catalysts, especially molybdenum borides that include α-MoB, β-MoB, Mo 2 B, and MoB 2 . , However, efforts to access high surface area metal boride materials are challenging, particularly for the molybdenum-based systems that are of greatest interest for their high activity and stability. The ability to access MXene-like 2D borides through etching boride analogues of MAX phases would significantly expand the diversity of available MXene materials .…”
mentioning
confidence: 99%
“…This step is required to preserve components from the reaction at the lower temperatures. 7), 14) For instance, Sitler et al 5) reported that solid-solution between ZrB 2 and HfB 2 can be obtained at temperatures as low as 1700°C. We prepared the binary equimolar solid-solution using similar conditions to ZHT20, to understand the formation of the ZHT diboride (Suppl 1).…”
Section: Resultsmentioning
confidence: 99%
“…By considering the high mutual solubility displayed by Zr-and Hfdiborides, the latter have been also combined in different proportions to form thermodynamically stable (Hf x Zr 1-x )B 2 solid solutions [5][6][7][8][9][10][11][12][13][14][15][16]. The methods proposed in the literature for their synthesis are chemical vapor deposition (CVD) [5,6], arc-melting [9], mechanically induced self-sustaining reaction [10], heat treatment of co-ball milled ZrB 2 and HfB 2 powders [11][12][13][14], molten salt route [15,16], carbothermal (CTR) and borohydride (BHR) reduction followed by flash sintering [7], and microwave co-assisted boro/carbothermal reduction [8]. Only few of them [7,[11][12][13][14] were addressed to the obtainment of bulk ceramics.…”
Section: Introductionmentioning
confidence: 99%